(untitled) (Globalization and Business, 2023)
Article analysis new technological opportunities for Georgia to reduce the Small and Medium size Enterprises (SME) financing gap, which hinders not only their own, but country’s economic development. While SME sector has a vital role in employment, inclusiveness, gross domestic product generation and etc. in any country in the world and especially in developing ones, they still face significant credit constraints having bank centered, non-diversified financial systems within their economies. However, modern digital financial technologies, could be seen as a paradigm changing instrument for Georgia. The reasons for the Fintech industry at the initial stage of its development in Georgia are different and mainly related toward (but not limited with): not enough legislative support so far; lack of financial education among society and even SME sector; low competition on the market; covid-19 global pandemic and related challenges; not enough motivation among businesses and businessmen to spend enough time, money and effort to innovate; lack of interest from the fintech industry because of small market size and etc.; decrease the foreign direct investments and increase the investment’s share in the banking sector and the absence of qualified workforce in needed amount.